Role of C-reactive protein in predicting the outcome of acute pancreatitis - S., Venkatesh; V., Neetha; S., Manish; B., Krishnan P. (International Surgery Journal, 2021)
Background: Acute pancreatitis is one of the most commonly encountered clinical entities in surgical practice and controversy still exists regarding the clinical features of acute pancreatitis. An early diagnosis, however, is regarded as mandatory for successful treatment. Over the years many Authors have proposed different scoring systems for the early assessment of the clinical evolution of acute pancreatitis. The most widely used scoring systems are often cumbersome and difficult to use in clinical practice because of their multi factorial nature. Thus, a number of unifactorial prognostic indices have been employed in routine hospital practice, such as C-reactive protein (CRP), serum amylase and serum lipase. These serum enzymes are easy to obtain in normal clinical practice and many authors consider them as reliable as multi factorial scoring systems. Methods: A hospital based observational prospective study was done with 30 patients to measure C reactive protein levels in patients of acute pancreatitis and evaluate if CRP levels predict the severity of pancreatitis. Results: In cases where CRP was raised >100 mg/dl on day 7 and beyond showed either a complication or increased duration of stay and delayed recovery. This correspondence of CRP with the clinical outcome co related well with other parameters like blood counts, serum lipase and amylase levels too. Conclusions: Hence, CRP can be a very useful uni factorial tool in assessing and thereby predicting the outcome in a case of pancreatitis.